A metaphylactic treatment with double dose oxytetracycline reduces the risk of bovine respiratory disease in feedlot calves - Fazzio, Luis Emilio (2015)
The objective of this study was to evaluate the effect of a metaphylactic treatment with oxytetracycline (OTC) in the labeled and double doses on the risk for bovine respiratory disease (BRD) in feedlot calves. This study was conducted in a commercial feedlot where 2,754 calves belonging to high risk groups were enrolled. A randomized complete block design was used, with animals as experimental units and pens (n=10) as blocks. Three experimental groups were assessed: 1- untreated control (CTL), 2- OTC 20 mg/kg SC (OTC20) and 3- OTC 40 mg/kg SC (OTC40). The risk for BRD was evaluated with a mixed logistic regression. Untreated CTL had 2.85 and 7.14 more chances of getting BRD than OTC20 and OTC40 groups, respectively (p<0.001). In conclusion, metaphylactic treatment with OTC is useful to reduce the risk for BRD in feedlot cattle, being protective effect higher at double dose than at labeled one.